Analysis Of Gross Domestic Product (Gdp) Sector On Tax Buoyancy Of Tax Havens Country In 2005-2019 - Wardi, Alya Putri; Rusydi, Mohammad Khoiru (Telaah Ilmiah Akuntansi dan Perpajakan, 2025)
Tax is one of the strategic revenue sources that can be used for the welfare and development of the country, so the government is making various efforts to increase tax revenue. The success of tax revenue performance can be seen through the value of tax buoyancy. Several previous studies have shown that the factors that can affect tax buoyancy are imports, the manufacturing sector, the service sector, the agricultural sector, and the level of corruption. This study aimed to determine the effect of the manufacturing, service, agricultural, and import sectors and the level of corruption on the level of tax buoyancy in Singapore in 2005-2013. This research uses a correlational quantitative approach. Secondary data is from a time series of data from 2005 to 2019 in Singapore. Data were obtained from the World Bank and the International Monetary Fund (IMF). Data analysis techniques include classic assumption tests, namely the normality test, linearity test, multicollinearity test, heteroscedasticity test, and autocorrelation test. Then, the Time Series Data Regression and F tests were carried out. The research shows that the Manufacturing and Service Seals affect Singapore's Tax Revenue. The Agricultural Sector, Import Sector, and the level of corruption do not affect Singapore's Tax Revenue. Abstrak  Pajak merupakan salah satu sumber penerimaan strategis yang dapat digunakan untuk kesejahteraan dan pembangunan negara, sehingga pemerintah melakukan berbagai upaya untuk meningkatkan penerimaan pajak. Keberhasilan kinerja penerimaan pajak dapat terlihat melalui nilai tax buoyancy. Beberapa penelitian terdahulu menunjukkan di antara faktor yang dapat mempengaruhi tax buoyancy adalah impor, sektor manufaktur, sektor jasa, sektor agrikultur, dan tingkat korupsi. Tujuan penelitian ini adalah untuk mengetahui pengaruh sektor manufaktur, sektor jasa, sektor agrikultur, sektor impot dan tingkat korupsi terhadap tingkat Tax Bouyancy di Singapura pada tahun 2005-2013. Penelitian ini merupakan menggunakan pendekatan kuantitatif korelasional. Data sekunder berupa data time series dari tahun 2005 2019 negara Singapura. Data diperoleh dari World Bank dan International Monetary Fund (IMF). Teknik analisa data meliputi uji asumsi klasik yaitu uji normalitas, Uji Linearitas, uji Multikolinearitas, uji heterokedastisitas, dan uji autokorelasi. Selanjutnya diilakukan Uji Regresi Data Time Series dan uji F. Penelitian menunjukkan bahwa Sektor Manufaktur dan Sektor Jasa berpengaruh terhadap Tax Revenue Singapura. Sektor Agricultural, Sektor Import dan tingkat korupsi tidak berpengaruh terhadap Tax Revenue Singapura.